2003
DOI: 10.1081/jas-120023584
|View full text |Cite
|
Sign up to set email alerts
|

Airway Responsiveness to Beta‐Adrenergic Agonist (Salbutamol) in Asthma

Abstract: Despite the controversy of airway responsiveness to beta2-agonist drugs in asthma, in a previous study we showed increased responsiveness of asthmatic airways to isoprenaline. Therefore, in the present study of airway sensitivity to other beta2-agonists, salbutamol and its relationship to histamine responsiveness was reexamined. The threshold bronchodilator concentrations of inhaled salbutamol required for a 20% increase in forced expiratory flow in 1 sec (FEV1), (PC20) was measured in 20 normal and 19 asthmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…Sixteen to twenty years after exposure, main respiratory complications were diagnosed as COPD (35%), bronchiectasis (32.5%), asthma (25%), large airway narrowing (15%), pulmonary fibrosis (7.5%), and simple chronic bronchitis (5%) (Hefazi et al, 2005). The concentration-response curves to salbutamol in chemical war victims of our previous study (Boskabady et al, 2008a) compared to normal subjects were different from those of smokers (Boskabady and Farhadi, 2005) but were similar to the asthmatic patients with similar FEV 1 level (Boskabady and Saadatinejad, 2003). There is no exact treatment for respiratory disorders induced by SM exposure.…”
Section: Cell Typementioning
confidence: 49%
“…Sixteen to twenty years after exposure, main respiratory complications were diagnosed as COPD (35%), bronchiectasis (32.5%), asthma (25%), large airway narrowing (15%), pulmonary fibrosis (7.5%), and simple chronic bronchitis (5%) (Hefazi et al, 2005). The concentration-response curves to salbutamol in chemical war victims of our previous study (Boskabady et al, 2008a) compared to normal subjects were different from those of smokers (Boskabady and Farhadi, 2005) but were similar to the asthmatic patients with similar FEV 1 level (Boskabady and Saadatinejad, 2003). There is no exact treatment for respiratory disorders induced by SM exposure.…”
Section: Cell Typementioning
confidence: 49%
“…Eosinophils in BAL may demonstrate the importance of asthma as one of the main pulmonary complications of chemical warfare [7]. The cause of reversibility in airway obstruction may be due to development of sulfur mustard gas-induced AHR, as AHR to brochodilators (isoprenaline and salbutamol) in asthmatic patients and its relationship to responsiveness to bronchoconstrictors (methacholine and histamine) were demonstrated previously [23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…The maximum response to methacholine and histamine was significantly greater in asthmatic than in normal subjects [24, 33]. In most control subjects, a plateau in concentration-response curves to methacholine and histamine was achieved; while in asthmatic patients, a plateau in the curves was not obtained, which is a characteristic feature of concentration response of asthmatic patients [34].…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42] In animal studies, propranolol has been shown to inhibit the benefit of VNS in reducing bronchoconstriction. 20 Asthma patients have also been reported to be more sensitive to endogenous epinephrine, 43 and at physiologic concentrations treatment with an epinephrine infusion can induce bronchodilation in a dose-dependent manner and at a dose below that which affects blood pressure and heart rates. 44,45 Furthermore, b-adrenoceptors have a higher affinity for epinephrine (K d = 0.8 lmol ⁄ L) than for the sympathetic neurotransmitter norepinephrine (K d = 10 lmol ⁄ L).…”
Section: Discussionmentioning
confidence: 99%